Are All Spatial Reference Frames Egocentric? Reinterpreting Evidence for Allocentric, Object-Centered, or World-Centered Reference Frames - Filimon, Flavia (Frontiers in Human Neuroscience, 2015)
The use and neural representation of egocentric spatial reference frames is well documented. In contrast, whether the brain represents spatial relationships between objects in allocentric, object-centered, or world-centered coordinates is debated. Here, I review behavioral, neuropsychological, neurophysiological (neuronal recording), and neuroimaging evidence for and against allocentric, object-centered, or world-centered spatial reference frames. Based on theoretical considerations, simulations, and empirical findings from spatial navigation, spatial judgments, and goal-directed movements, I suggest that all spatial representations may in fact be dependent on egocentric reference frames.